The Human Right to Education, the Ethical Responsibility of Curriculum, and the Irony in “Safe Spaces” .......... 407 - Preez, Petro du (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
Scholarly explorations have revealed that neither “education” nor “rights” are static concepts and that their varying interpretations have a direct influence on the way we understand the right to education. This paper will, firstly, aim to contribute to a more nu-anced understanding of education and rights. Secondly, this paper will attend to the plea of curriculum renewal and the ethical turn in the study of curriculum that necessitates us to rethink how we curriculate and to think about our ethical responsibilities where the right to education is concerned. Lastly – based on literature that indicates that the use of the notion of safe spaces is often ambiguous – the implications of the right to education and the ethical responsibility of curriculum will be discussed in the context of the notion “safe spaces”.